2008
DOI: 10.1016/j.psychsport.2007.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and physical self-concept among sedentary adolescent females: An intervention study

Abstract: PROBLEM: Physical activity has been promoted as a means of enhancing self-concept, yet the evidence for this connection is far from compelling. In particular, experimental research investigating this association during adolescence, a period during which many youth struggle to maintain a positive self-image, is noticeably lacking. This study investigates the impact on self-concept of a 9-month physical activity intervention among sedentary adolescent females. METHOD: Female adolescents who were sedentary at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 38 publications
10
79
1
9
Order By: Relevance
“…Several researchers have documented that athlete have higher self-concept as compared to non-athlete [26,29,[30][31]. Self-selection may be the main cause of these differences.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Several researchers have documented that athlete have higher self-concept as compared to non-athlete [26,29,[30][31]. Self-selection may be the main cause of these differences.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…In the similar study Hays et al (17) also found same results. Schneider et al (35) in a study were examined the effect of physical activity on physical self-concept. Participants were required to meet the insufficient physical activity to maintain fitness, and ability to exercise.…”
Section: Physical Activity and Physical Self-conceptmentioning
confidence: 99%
“…While current literature supports physical exercise as a means to promote life satisfaction (Rejeski & Mihalko, 2001), physical self-concept (Faria & Silva, 2000;Schneider, Dunton, & Cooper, 2008), and perception of one's health status (Greenspan et al, 2007), few studies have focused on the relationship between mind-body exercise programs and these outcomes in healthy females.…”
Section: Introductionmentioning
confidence: 99%